A hope for ineffective antibiotics to return to treatment: investigating the anti-biofilm potential of melittin alone and in combination with penicillin and oxacillin against multidrug resistant-MRSA and -VRSA - Jalalifar, Saba; Razavi, Shabnam; Mirzaei, Rasoul; Irajian, Gholamreza; Pooshang Bagheri, Kamran (Frontiers in Microbiology, 2024)
The emergence of multi-drug resistant bacterial strains have posed a significant challenge in community due to their ability to form biofilm and develop resistance to common antibiotics. Accordingly, we aimed to investigate the antimicrobial and antibiofilm effects of melittin AMP, both alone and in combination with penicillin and oxacillin, against biofilm-forming multidrug-resistant (MDR)- MRSA and -VRSA. We investigated the kinetics of biofilm formation and assessed various parameters including: the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), Fractional Inhibitory Concentration Index (FICi), and Fractional Bactericidal Concentration Index (FBCi), and the antibiofilm activity of melittin and antibiotics indicated by the Minimum Biofilm Inhibitory Concentration (MBIC), Minimal Biofilm Eradication Concentration (MBEC), Fractional Biofilm Inhibitory Concentration Index (FBICi), and Fractional Biofilm Eradication Concentration Index (FBECi). The geometric means of the MIC values for penicillin, oxacillin, and melittin were 19.02, 16, and 1.62 µg/ml, and for MBC values were 107.63, 49.35, and 5.45 µg/ml, respectively. The melittin-penicillin and melittin-oxacillin combination indexes based on FIC values were 0.37 and 0.03, and based on FBC values were 1.145 and 0.711, respectively. Melittin inhibited the biofilm formation with MBIC values ranging from 10 to 1.25 μg/mL, and MBEC values ranging from 40 to 10 μg/mL. Melittin-penicillin and melittin-oxacillin combination indexes based on FBIC values were 0.23 and 0.177, and based on FBEC values were 5 and 2.97, respectively. In conclusion, melittin has the potential to revive beta-lactam antibiotics against MRSA and VRSA and is an innovative approach against antibiotic-resistant bacteria.